Distal intestinal obstruction syndrome in cystic fibrosis: presentation, outcome and management in a tertiary hospital (2007–2012). Issue 10 (18th November 2013) - Subhi, Rami; Ooi, Rachel; Finlayson, Felicity; Kotsimbos, Tom; Wilson, John; Lee, Wei Ran; Wale, Roger; Warrier, Satish
Abstract Background Cystic fibrosis (CF) can result in distal intestinal obstruction syndrome (DIOS) due to inspissated mucus. This paper describes the clinicopathological characteristics of adult CF patients with DIOS and assesses risk factors for surgery. Methods A retrospective audit of CF patients at the Alfred Hospital from January 2007 to February 2012 was carried out. Patients who had 'bowel obstruction or constipation' were abstracted from the database, and medical records were reviewed for a diagnosis of DIOS. Results Forty‐five encounters of 35 patients were extracted. Twenty‐five (83%) patients were homozygous for the delta F508 mutations, 29 (85%) had pancreatic insufficiency and 15 (44%) had a lung transplant. Patients presented with abdominal pain (96% of encounters), nausea (76% of encounters) and vomiting (67% of encounters). Computed tomography (CT) was performed in 20 episodes. Compared with CT, abdominal X‐ray had a sensitivity of 63% (95% confidence interval (CI) 30–89%) and specificity of 33% (95% CI 8–70%) for detecting DIOS with obstruction. Forty‐one (91%) encounters resolved with medical management within 2–3 days. Three patients required surgical intervention in four episodes. Previous laparotomy (odds ratio (OR) 28.5, 95% CI 1.3–624, P = 0.03) and history of meconium ileus (OR 14, 95% CI 1–192, P < 0.05) were statistically significant predictors of progression to surgical management. Conclusion In most patients with DIOS, the obstruction resolves with medical management. Early consultation with a CF service, assessment for a surgical abdomen and involvement of surgeons where appropriate is recommended. A history of previous laparotomy is a risk factor for the need for surgical intervention.